Regulating mineralization rates of Tithonia diversifolia and Lantana camara prunings to improve phosphorus availability in calcareous soils - Y Nuraini; N Sukmawatie (Brawijaya University, 2014)
The effect of mixing of Tithonia diversifolia and Lantana camara prunings to improve synchronization between P released from the prunings with crop demand for P was studied in a laboratory and in a glasshouse. Tithonia diversifolia prunings (Td), Lantana camara prunings (Lc), and farmyard manure (Pk) were thoroughly mixed with the proportion (% of dry weight) of; 25Td +75 Lc ; 50Td +50 Lc ; 75Td +25 Lc ; 90Lc +10 Pk ; 45Td +45 +10 Lc Pk ; 100Td and 100Lc, and then mixed with 100 g of air-dried soil with a rate equivalent to 100 kg P / ha. Results of the study showed that the pruning mixtures decomposed and mineralized faster than that of Lantana camara pruning only, but slower than that of Tithonia diversifolia pruning only. The amount of P released from the pruning mixtures increased with increasing proportion of Tithonia diversifolia pruning in the mixtures. Increasing proportion of Tithonia diversifolia pruning in the mixture applied to the soil increased the amount of P taken up by maize.